Role of Antiepileptic Drugs in Migraine Prevention - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Abnormal brain excitability as a migraine trigger mechanism, and the use of antiepileptic drugs (AED) in migraine prevention, are reviewed from The Chicago Medical School, North Chicago, IL.